RELATION BETWEEN PULSE WAVE AND HEART FAILURE IN HYPERTENSIVE PATIENTS. (June 2018) - Alcantara, C.; Alcantara, P.; Ramalhinho, V.; Veloso, F.; Moreira, C. Santos
Abstract : Objective: The increased central aortic stiffness has been identified as an independent risk factor for heart failure and end-organ damage. Carotid-femoral pulse wave velocity (PWV) measures the stiffness over large part of the aorta, and objective of this study is evaluate the relation between carotid-femoral pulse wave and cardiac parameters. Design and method: We compared three groups of hypertensive patients with the same age and sex: SD - with systolic dysfunction, DD - with diastolic dysfunction and NLV - with normal LV function. All participants underwent a comprehensive echocardiographic study including carotid artery sonography, and assessments of arterial stiffness and wave reflections. Patients with uncontrolled hypertension, uncontrolled diabetes mellitus, recent myocardial infarction (within 3 months), atrial fibrillation, valvular heart disease, recent stroke (within 3 months) or established peripheral artery disease were excluded. The model was ANOVA oneway and regression analysis. Results: There are no differences in sex, office and ambulatory Diastolic Blood Pressure (DBP). The office and ambulatory systolic blood pressure (SBP), aortic systolic (ASBP) and diastolic blood pressure (ADBP) are different among the three groups (SD SBP 118.2 ± 18.6; DD SBP 136.1 ± 21.3; NLV SBP 128.7 ± 18.3, p < 0, 01), (SD ASBP 108.8 ± 17.6; DD ASBP 124.1 ± 20.4; NLV ASBP 116.8 ± 16.2, p < 0, 01), (SD ADBP 65.4 ± 9.5; DD ADBP 80.1 ± 11.1; NLV ADBP 73.1 ± 11.7, p < 0, 01). The carotid-femoral pulse wave velocity were different (SD PWV 12.7 ± 4.3; DD PWV 13.6 ± 4.1; NLV PWV 11.6 ± 3.3, p < 0, 01) and central augmentation index (SD CAI 23.2 ± 14.1; DD CAI 26.2 ± 13.5; NLV CAI 21.3 ± 13.3, p < 0, 01). We found a relation between PWV and left ventricular mass index, and between CAI and relation A/E waves and E/E[Combining Acute Accent]. Conclusions: The present study expanded the usefulness of carotid-femoral pulse wave velocity and central augmentation index as a risk factor for cardiovascular disease in patients with advance disease. We found that these parameters can be used to establish a relation to cardiac function in patients with hypertensive disease and could be used to predict the vascular lesions that these patients might have.